Cough sensitivity to mannitol inhalation challenge identifies subjects with chronic cough. Issue 5 (17th May 2018) - Koskela, Heikki O.; Lake, Clair; Wong, Keith; Brannan, John D.
Cough is the most common reason why people seek medical attention [1]. Cough hypersensitivity syndrome (CHS) is a new concept to describe a condition with long-standing hypersensitivity of vagal afferent nerves or an alteration of the central processing of their input regardless of the underlying cause [2]. The current definition of CHS is purely clinical; however, a test capable of demonstrating this hypersensitivity both reliably and feasibly might be used as a diagnostic test for CHS. Mannitol challenge is a promising diagnostic test for cough hypersensitivity syndrome http://ow.ly/gWf530j9O7H